63 Increased risk of acute st-segment myocardial?infarction in female smokers – a?contemporary demographic study. (5th June 2017) - Palmer, James; Lloyd, Amelia; Steele, Lloyd; Fotheringham, James; Teare, Dawn; Iqbal, Javaid; Grech, Ever
Abstract : Background: Studies have shown that smoking increases the risk of acute ST-segment elevation myocardial infarction (STEMI). However, the impact of gender on this risk is unknown. Methods: This retrospective ecological cohort study examined all patients presenting with acute STEMI undergoing primary percutaneous coronary intervention at the South Yorkshire Cardiothoracic Centre (UK) between 2009–14. Index cases were compared to population data from the UK Office for National Statistics for smoking status, gender and age. Incidence rates of STEMI for current and non-smokers were calculated by gender and their associated 95% confidence intervals (CI) determined from the Poisson distribution. Age-standardised incidence rate ratios (IRR) comparing STEMI rates between smokers and non-smokers were calculated between genders in three age groups (18–49, 50–64, >65). Results: There were 2, 996 STEMI patients. 27.1% were female, who were significantly older than male patients (mean age: 66.3 vs 60.9, p=0.03). Risk factor prevalence was similar between genders, although hypertension was more common in females (44.9% vs 36.7%, p<0.001). In current smokers, the peak STEMI rate in females was in the 70–79 age range (233/100, 000 pt/yrs) and the 50–59 (458/100, 000 pt/yrs) in males. Across all ages, smokers had a significantly higher acute STEMI risk with an IRR of 5.11 (CI: 4.83–5.40). Compared to their non-smoking gender counterparts, females had a significantly higher IRR than males (6.62 (CI: 5.91–7.38) vs 4.46 (CI: 4.18–4.76)), and this difference was significant in all three age groups. The highest IRR was in female smokers in the 18–49 group at 12.67 (CI: 9.69–16.28), vs 8.47 (CI: 7.50–9.53) in males. The most striking difference between genders was in the 50–64 group (IRR 11.03 (CI: 9.33–12.96) vs 4.63 (CI: 4.21–5.08)). Conclusion: Smoking status had a significantly differential effect between genders, with female smokers at increased risk of acute STEMI over male smokers by a factor of 1.48. Young female smokers (18-49) had the highest IRR and were over 12 times more likely to suffer an acute STEMI than their non-smoking peers. The largest IRR gender difference, by a factor of 2.38, was in the 50–64 age group.